THE EFFECT OF ENGLISH GRAMMAR TEST APPLICATION ON STUDENTS’ GRAMMAR MASTERY OF SIMPLE PAST TENSE AT THE EIGHTH GRADE OF JUNIOR HIGH SCHOOL - Dinda Dwi Tifani (BRIGHT VISION Journal of Language and Education, 2022)
The objective of this study is to find out whether there is a significant effect of English Grammar Test (EGT) application on students’ grammar mastery of simple past tense at the eighth grade of Junior High School. Quantitative research method with quasi-experimental design was used in this research. It was conducted at the eighth grade of MTs. Islamiyah Perkebunan Tanjung Kasau. The population consisted of 60 students from two classes. Using saturation sampling method, the two classes namely VIII-A and VIII-B were selected as the sample of this study with each class consisted of 30 students. Furthermore, VIII-A class was selected as control class and VIII-B class as experimental. In collecting the data, multiple choice and “fill in the blank” test forms were used in this study. The tests were then distributed in two ways; 1. Pre-test was distributed before the treatment: 2. Post- test was distributed after the treatment. Furthermore, the data was analyzed by using statistical formulation and Microsoft Excel 2013 with 0,05 significance level. After the data was analyzed, it can be found that the value of tobserved was higher than ttable. It can be seen from tobserved (3,839) > ttable (2,001) at the degree of freedom (df) = 58. It means that the alternative hypothesis (Ha) was accepted and null hypothesis (H0) was rejected. Therefore, it can be concluded that English Grammar Test application gives significant effect on students’ grammar mastery of simple past tense at the eighth grade of MTs. Islamiyah Perkebunan Tanjung Kasau.